Membangun Kapasitas UMKM dalam Pemasaran Digital di Desa Wisata Way Tebing Cepa - Yusda, Desi Derina; Indriyani, Susi; Enzovani, Senna; Loliyani, Rini; Brajanoto, Destoprani (Fakultas Teknik Universitas Palangka Raya, 2024)
The Covid-19 pandemic has severely hampered the expansion of the world economy, including Indonesia. In the midst of this challenging situation, businesses are being forced to innovate and fight for their survival. On a positive note, the rapid advancement of digital technology has opened up new opportunities for MSMEs to market their products to a wider audience online. This allows MSMEs to reach a broader market and increase sales. However, to fully capitalize on these opportunities, MSMEs need to improve their human resources (HR) and information technology (IT) capabilities. This is crucial to help them adapt to the various new technologies emerging in the era of Industry 4.0. The government has high hopes for MSMEs to become major players in the development of Indonesia's digital economy. MSME empowerment can be achieved by assisting them in gaining access to finance and ensuring that their products are of sufficient quality to compete in the market. This can increase investor confidence in MSMEs and open up funding opportunities. To enter the online business, MSMEs need to make improvements in several areas, such as product quality, product standardization, HR development, and access to financing. Collaboration between the government and e-commerce platforms is essential to support MSMEs in utilizing digital technology and developing their online businesses. As a commitment to helping MSMEs, Universitas MItra Indonesia is conducting a community service activity with the theme